Tantangan Humanisme bagi Pendidikan Agama Kristen Abad 21 dan Tanggap Teologisnya - Leniwan Darmawati Gea; I Putu Ayub Darmawan (UKI Press, 2021)
Education aims to shape human beings to grow in a better direction, in accordance with what is expected in social life. That is why educational institutions design curricula necessary for this purpose. However, in its development, a big challenge arises behind the good goals that were originally expected, namely from the ideology of humanism which makes humans become autonomous with all their abilities and advantages, so that humans no longer need God in all aspects of their life. This fact is a big challenge for Christian education which leads to the truth of God, so it is very necessary to be addressed. From these problems, the authors conducted research with a literature analysis approach. There are two dangers of humanism for Christian religious education. First, humans become the main center of education so that humans leave the importance of spiritual life and knowledge of God; Second, the misconception about sin, where sin is seen not as a big problem that needs to be resolved. In the midst of these challenges, Christianity must be critical of the curricula in force so as to maintain efforts to internalize Christian values ​​through education.